NON PARTISIPASI MASYARAKAT PADA PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH (WALIKOTA) KOTA PEKANBARU TAHUN 2011 DI KELURAHAN CINTA RAJA KECAMTAN SAIL - Vanny Vindrya; M. Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Election of Regional Head and Deputy Head of Pekanbaru in 2011 experienced a significant decline in giving the right to vote in the General Election. The phenomenon of low community participation in Election of Regional Head and Deputy Head (Mayor) Kota Pekanbaru dated May 18, 2011 in the Village District of Sail King of Love is based on data obtained showed 38.62% of the voters list (DPT) which does not give the right suranya. It is a form of disappointment experienced by the people against the government and prospective leaders can not changes in the field of life towards a better direction. Most people feel by the behavior of the government and legislators who pay less attention to the people and fight for their interests.The purpose of this study was to determine the characteristics of respondents who did not choose and what factors are causing the people who have registered as voters list (DPT) did not vote in the elections in the Village District of Sail Love King by using the theory of participation. This research study merupakakan Quantitative Descriptive, then for the data analysis techniques presented in tabular form. This study aimed to use your questionnaire and observation to obtain information in the study.Based on the research that has been described, it is known that factors that affect people who have registered as voters list (DPT) did not vote in the elections in 2011 are due to the apathy of society, cynicism, alienation and anomiKeyword : NonParticipation, Election, and Final Voters List (DPT)